Debating the past : music, memory, and identity in the Andes - Romero, Raúl R. (Oxford University Press, 2001)
This volume examines how the search for "cultural authenticity," the dispute over the past, and the role of "modernity" have been instrumental in building the regional musical culture of the Mantaro Valley, a central Peruvian region with about half a million inhabitants. How these people have addressed concerns over the loss of ancient traditions by restructuring colonial and pre-Hispanic traditions into new contexts and forms is explored. Covering private and public music making, along with ritual, ceremonial, and popular uses of music, Romero studies the interaction of mu